Performance of different colorectal cancer screening strategies: a long-term passive follow-up population-based screening program in Beijing, China - Xi Zhang; Lei Yang; Shuo Liu; Huichao Li; Qingyu Li; Haoxin Li; Ning Wang; Jiafu Ji (BMC, 2023)
Abstract Background We aimed to assess the performance of the risk assessment questionnaire and fecal immunochemical test (FIT) in a population-based colorectal cancer (CRC) screening program to provide timely evidence for tailored screening strategies in China. Methods This analysis was conducted using data from Beijing Cancer Screening Prospective Cohort Study (BCSPCS). A risk assessment questionnaire and FIT were selected as the primary screening methods, and participants with any positive results were referred to undergo a diagnostic colonoscopy. Results From 2015 to 2020, 148,636 Beijing residents aged 40-69 years were invited from designated communities, with 147,807 finishing the risk assessment questionnaire and 115,606 (78.2%) completing the FIT. Among the 42,969 (29.1%) high-risk CRC participants, 23,824 (55.4%) underwent colonoscopy. One year after enrollment, all subjects were linked to the Beijing Cancer Registry (BCR) database and 241 cases of CRC were confirmed. The CRC incidence rate was 58.2/100,000 for the low-risk arm and 418.9/100,000 for the high-risk arm. For participants who underwent colonoscopy, 91 CRC cases were detected, with a detection rate of 91.9% and 63.7% of them were early-stage cases. Furthermore, the sensitivities of utilizing the risk assessment questionnaire alone, FIT alone, combined risk assessment questionnaire and FIT were 75.7%, 50.1%, and 95.1%, and the specificities were 75.3%, 87.3%, and 70.7%, respectively. Conclusion The Beijing CRC screening program can effectively detect early-onset CRC; however, the compliance with colonoscopy still needs to be improved.